Evaluation of Void Nucleation and Development during Plastic Deformation of Dual‐Phase Steel DP600. Issue 12 (4th April 2016) - Isik, Kerim; Gerstein, Gregory; Clausmeyer, Till; Nürnberger, Florian; Tekkaya, A. Erman; Maier, Hans Jürgen
Abstract : This paper presents investigations on the characterization of ductile damage and identification of the porosity‐related material model parameters in a dual‐phase steel DP600. As a modeling reference for the damage evolution, a variant from the Gurson model family is taken. The micromechanical investigations related to nucleation and growth of voids have been carried out. In order to show the void‐volume evolution during the deformation, post‐mortem scanning electron microscope (SEM) analysis of a notched tensile test is used. Using the ion beam slope cutting methodology to prepare the specimens for SEM analysis, the microstructure can be observed in 2D including the voids. In this way, for the dual‐phase steel, characteristic damage behavior upon deformation due to interaction of martensite and ferrite can be investigated. The minimum void size (areal) that can be measured is 0.05 µm 2 . This resolution of the measurements provides the detection of the newly nucleated voids. For the related material parameters, void‐size relevant criterion is applied to determine the newly nucleated voids at a certain plastic strain. Abstract : The evolution of voids in a dual‐phase steel, DP600 (containing ferrite matrix and martensite), is investigated by scanning electron microscopy. The specimens prepared by ion beam slope cutting are used to observe small voids (minimum area 0.05 μm 2 ). The quantitative evaluation of the void volume fraction enables the identification of material parameters for a Gurson‐type model.